Utilizing GP 2 for Restaurant Recommendation - Nitamayega; Gia Septiana Wulandari; Kemas Rahmat Saleh Wiharja (Indonesia Journal on Computing (Indo-JC), 2024)
The increasing diversity of food and beverage providers poses a challenge for people to find a restaurant that aligns with their preferences. Restaurant recommendation systems can address this problem by providing accurate and relevant suggestions. Although there are many previous studies have explored various recommendation methodologies, the utilization of knowledge graph implemented with GP 2 is still limited. Knowledge graphs can represent complex information in a structured way, while GP 2 is a graph-specific programming language that has a simple syntax. This research focuses on the implementation of a knowledge graph-based restaurant recommendation system with GP 2. The recommendation scheme built can provide the best accuracy, reaching 84.97%. This shows that the knowledge graph-based restaurant recommendation system with GP 2 can demonstrate the effectiveness of the system in providing accurate and relevant recommendations, showing the potential of knowledge graph and GP 2 for the development of recommendation systems in the future and being an effective solution to overcome recommendation problems.